Complementary Feeding-A Challenge to Be Addressed in Rural Uttar Pradesh, India - Garg, Aashima; Chadha, Ravinder (Pakistan Journal of Nutrition, 2009)
Sir, Lack of appropriate complementary feeding (CF), defined as one which is timely, adequate, safe and properly fed (WHO, 2001), is a problem which directly or indirectly contributes to malnutrition, infectious illness and mortality in infants. The incidence of malnutrition rises sharply between the ages of 6-18 months (WHO, 2001) with maximum undernutrition occurring at 8-11 months of age (Vir, 2001). The NFHS-2 (1998-99) also reports a 5 fold increase in undernutrition prevalence from 6 months to 23 months of age.